2017
DOI: 10.2217/nnm-2017-0241
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Alterations Induced By Transient Exposure of MCF-7 Cells to Maghemite Nanoparticles

Abstract: Transient exposure to MNP-CIT promoted epigenomic changes and altered the DNMT genes regulation in MCF-7 cells. These events should be considered for biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The only report concerning the impact of AuNPs on DNA methylation shows the induction of methylation of several genes in mouse lungs in vivo [17]. Similarly, the only report regarding SPIONs’ impact on DNA methylation shows that maghemite (γ-Fe 2 O 3 ) nanoparticles did not affect global DNA methylation in MCF-7 cells, but affect the methylation of several specific genes [33]. It seems that the impact of nanoparticles on DNA methylation is cell-type-specific and highly dependent on the properties of the nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only report concerning the impact of AuNPs on DNA methylation shows the induction of methylation of several genes in mouse lungs in vivo [17]. Similarly, the only report regarding SPIONs’ impact on DNA methylation shows that maghemite (γ-Fe 2 O 3 ) nanoparticles did not affect global DNA methylation in MCF-7 cells, but affect the methylation of several specific genes [33]. It seems that the impact of nanoparticles on DNA methylation is cell-type-specific and highly dependent on the properties of the nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, literature on the epigenetic effects of SPIONs is very limited. It has been reported that Fe 2 O 3 SPIONs affect miRNA expression in NIH/3T3 cells [9] and DNA methylation in MCF-7 cells [33]. Epigenetic effects of Fe 3 O 4 SPIONs have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that short-term exposure to engineered NM modestly affected DNA methylation within the most abundant transposable elements [7]. A detailed DNA methylation profile of DNA methyltransferase genes in breast cancer cell line MCF-7 after treatment with maghemite nanoparticles revealed epigenetic changes, even though the overall percentage of DNA methylation was not affected [8], which in contrast to altered global methylation by the same nanomaterial but in human submandibular gland cells, which was analyzed in a later study [9]. No significant differences in the DNA methylation status of inflammatory and apoptosis response genes of human liver cancer cells (HepG2) was found after silver, gold and superparamagnetic iron nanoparticle (SPION) exposure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, citrate detachment from the surface of MNPs under physiological conditions is negligible, and the physical-chemical characteristics of citrate-capped MNPs can be preserved over years. 21,27 Indeed, previous in vivo investigations have shown the biocompatibility and nonmutagenic effects of citrate coatings, [28][29][30] in spite of adverse effects described in in vitro tests. 31 However, citrate-coated MNPs can be colloidally unstable in a biological system when dispersed in a medium with high ionic strength, such as PBS buffer.…”
Section: Discussionmentioning
confidence: 99%